Computational and cognitive approaches to narratology - Ogata, Takashi 1958-; Akimoto, Taisuke 1984- (Information Science Reference, an imprint of IGI Global, 2016)
This book discusses issues of narrative-related information and communication technologies, cognitive mechanism and analyses, and theoretical perspectives on narratives and the story generation process